Case report: A case of acute pancreatitis with myocarditis and thyrotoxicosis - Fu, Qiuyu; Cui, Jianing; Zhang, Yanli; Liu, Jiamian; Zhang, Xiaoqiang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundA variety of diseases can complicate acute pancreatitis and myocarditis. As acute pancreatitis combined with myocarditis and thyrotoxicosis is rare, we report a case of acute pancreatitis combined with myocarditis and thyrotoxicosis.Case presentationWe present a case of a previously healthy 37-year-old male who was admitted with epigastric pain; elevated blood amylase, lipase, and cardiac enzymes; markedly abnormal thyroid function; and an electrocardiogram showing elevated ST segments. He was diagnosed with acute pancreatitis combined with myocarditis and thyrotoxicosis. After 10 days of treatment, his epigastric pain disappeared. Further, his clinical test indices and electrocardiogram results returned to normal. The patient was free of abnormalities at the one-month follow-up, and his prognosis was good.ConclusionAcute pancreatitis can be complicated by myocarditis and thyrotoxicosis. The aetiology and pathogenesis are unknown and warrant further study.